Signing international treaties of Human Rights in Argentina. Part I: Neoliberal model of the ’90 - Parisí, Elio Rodolfo; Manzi, Adrian (Nómadas. Critical Journal of Social and Juridical Science, 2013)
Many historians agree that the implementation of neoliberal measures, within Latin America, had as objective to discipline the working populations, not in terms of behavioral control, but rather in terms axiological, introducing to the global market (supply-demand) as a new moral value. Will be discussed that with the launching of the Structural Adjustment Plans during the ’90 in relation to the constitutional reforms that will apply from 1994 with the signing of international treaties by the Argentine State. The glimpse of court action as a growing field led us to analyze this system under the Foucaultian methodology, in its structural logic rather than on the meanings and significance of the values that are the rules. For Foucault, the question is more focus on capillary relations of domination, because he didn’t envision what holds power, or what you want, but to distinguish how they were and collective efforts to make the relationship of power is transferred to the field of justice. Question makes us think about the subjetivante effect of the Argentine human rights system, the way to establish contact with any officer of justice.